2019
DOI: 10.1055/s-0039-1696610
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Posterior Fossa Hematoma, A Rare Entity: Study of 21 Cases

Abstract: Background Traumatic posterior fossa hematoma is a rare entity. Traumatic posterior fossa hematomas are associated with considerable morbidity and mortality and their surgical management remained controversial. Methods From August 2011 to August 2017, approximately 5,100 patients with head injury were managed. Authors reviewed clinical and radiological findings, management criteria, and outcome of posterior fossa hematoma in 21 patients. Results Out of 21 cases, 13 survived with our management. The Glasgow C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…In accordance with previous studies on this topic our data showed GCS at initial presentation to be the most predictive clinical tool 5,6,7,21,23,25 . Domenico d'Avella et al 7 suggest that A GCS score of less than 8 was the most powerful adverse prognostic factor (58.78% probability of poor outcome as sole covariate) .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In accordance with previous studies on this topic our data showed GCS at initial presentation to be the most predictive clinical tool 5,6,7,21,23,25 . Domenico d'Avella et al 7 suggest that A GCS score of less than 8 was the most powerful adverse prognostic factor (58.78% probability of poor outcome as sole covariate) .…”
Section: Discussionsupporting
confidence: 93%
“…In this study fall from bike and pillan rider are the most common mechanism of injury. Bhardwaj et al has 15/21( 71.14%) 5 , Harsh et al has 15/23 ( 65.21%) 23 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations